Recent results from the Arctic Radiation and Turbulence Interaction STudy (ARTIST) project - Nardino, M.; Bonafè, U.; Calzolari, F.; Georgiadis, T.; Levizzani, V.; Orsini, A.; Ravegnani, F.; Trivellone, G. (Societa italiana di fisica, 2002)
Ground-based measurements were conducted at Ny-˚Alesund in the Svalbard Islands in the framework of the research project ARTIST (Arctic Radiation and Turbulence Interaction STudy) funded by the European Communities. Key objectivesof the campaign were: 1) provide all participantswith ground reference data as input to models describing the development of the atmospheric boundary level, 2) compute the surface roughness length in order to characterise the surface of the site, 3) parameterise the surface energy exchanges, calculating the surface radiation flux, the sensible and latent heat fluxes, and 4) obtain the surface energy balance during both clear and cloudy sky conditions. The cloud radiative forcing has been also estimated. Final results of the analysis of the data set are presented.